KEGIATAN SENAM ICE BREAKING DALAM PENGEMBANGAN KECERDASAN KINESTETIK ANAK USIA DINI - Yeni Maryani; Sharina Munggaraning Westhisi (IKIP Siliwangi, 2021)
This study aims to determine the process of implementing ice-breaking gymnastics activities in the development of early childhood kinesthetic intelligence. Ice-breaking gymnastics activities are carried out when the activities line up. The duration of ice-breaking gymnastics activities is only 3-5 minutes so that the children are enthusiastic to participate in these activities. The implementation of ice breaking gymnastics is done routinely to train the gross motor stimulation of children in the development of early childhood kinesthetic intelligence. This research uses descriptive qualitative research methods. The subjects in this study are group B students. The data collection techniques are interviews, observation, and documentation. Based on the results of the thematic analysis and discussion, it can be concluded that the ability of children's kinesthetic intelligence can be improved through ice-breaking gymnastics activities, through these gymnastics activities can stimulate the intellectual abilities of body movements, and can train their physical abilities through ice-breaking gymnastics with simple movements that are easy to imitate, does not drain energy and contains elements of joy and joy accompanied by songs and musicPenelitian ini bertujuan untuk mengetahui proses pelaksanaan kegiatan senam ice breakingdalam pengembangan kecerdasan kinestetik anak usia dini.Kegiatan senam ice breakingini dilakukan pada saat kegiatan berbaris.Durasi kegiatan senam ice breakinghanya 3-5 menit sehingga anak-anak antusias untuk mengikuti kegiatan tersebut.Pelaksanaan senam ice breakingini dilakukan secara rutin agar melatih stimulasi motorik kasar anak dalam pengembangan kecerdasan kinestetik anak usia dini.Penelitian ini menggunakan metode penelitian deskriptif kualitatif dengan teknik analisis tematik. Subjek dalam penelitian ini siswa kelompok B dan dua Guru kelas. Teknik pengumpulan data ini adalah wawancara, observasi, dan dokumentasi. Berdasarkan hasil analisis data tematik dan pembahasan maka dapat disimpulkan bahwa kemampuan kecerdasan kinestetik anak dapat ditingkatkan melalui kegiatan senam ice breaking, melalui kegiatan senam ini dapat menstimulasi kemampuan kecerdasan gerak tubuh, serta dapat melatih kemampuan fisiknya melalui senamice breaking dengan gerakan-gerakan sederhana yang mudah ditirukan, tidak menguras energi serta mengandung unsur kegembiraan dan keceriaan dengan di iringi oleh lagu dan musik.